Immune Cell Infiltration in Malignant Middle Cerebral Artery Infarction: Comparison with Transient Cerebral Ischemia. Issue 3 (March 2014) - Chu, Hannah X; Kim, Hyun Ah; Lee, Seyoung; Moore, Jeffrey P; Chan, Christopher T; Vinh, Antony; Gelderblom, Mathias; Arumugam, Thiruma V; Broughton, Brad RS; Drummond, Grant R; Sobey, Christopher G
We tested whether significant leukocyte infiltration occurs in a mouse model of permanent cerebral ischemia. C57BL6/J male mice underwent either permanent (3 or 24 hours) or transient (1 or 2 hours+22- to 23-hour reperfusion) middle cerebral artery occlusion (MCAO). Using flow cytometry, we observed ∼15, 000 leukocytes (CD45 +high cells) in the ischemic hemisphere as early as 3 hours after permanent MCAO (pMCAO), comprising ∼40% lymphoid cells and ∼60% myeloid cells. Neutrophils were the predominant cell type entering the brain, and were increased to ∼5, 000 as early as 3 hours after pMCAO. Several cell types (monocytes, macrophages, B lymphocytes, CD8 + T lymphocytes, and natural killer cells) were also increased at 3 hours to levels sustained for 24 hours, whereas others (CD4 + T cells, natural killer T cells, and dendritic cells) were unchanged at 3 hours, but were increased by 24 hours after pMCAO. Immunohistochemical analysis revealed that leukocytes typically had entered and widely dispersed throughout the parenchyma of the infarct within 3 hours. Moreover, compared with pMCAO, there were ∼50% fewer infiltrating leukocytes at 24 hours after transient MCAO (tMCAO), independent of infarct size. Microglial cell numbers were bilaterally increased in both models. These findings indicate that a profound infiltration of inflammatory cells occurs in the brain early after focal ischemia, especially without reperfusion.